Analysis of Factors Affecting Compliance With Hand Hygiene Among Medical Staff at The Health Center - Lucky Sandi Centaury; Chairil Zaman; Akhmad Dwi Priyatno; Dianita Ekawati (School of Health Sciences Al-Ma'arif, 2025)
Carrying out the profession as medical personnel, there is a high possibility of direct or indirect contact with microorganisms, so that medical personnel are prone to cross-contamination between patients and medical personnel. This study aims to determine the description of compliance with hand hygiene among respondents at the Nibung Health Center, North Musi Rawas Regency in 2024. The design in this study is an analytical survey with a cross sectional design, using the chi-square test. sampling using total sample technique. The results obtained from each variable are age 0.028 ≤ α 0.05, gender p value 0.312 ≥ 0.05, education with compliance p value 0.021 ≤ 0.05, knowledge p value 0.012 ≤ 0.05, attitude p value 0.003 ≤ 0.005, availability of facilities p value 0.713 ≥ 0.05, the role of PPI p value 0.032 ≤ 0.05. The conclusion is that there is a relationship between age, education, knowledge, attitude, and the role of PPI with compliance with hand hygiene. It is hoped that the Nibung Health Center, North Musi Rawas Regency, will increase staff compliance in the application of daily hand hygiene with the indication of “five moments”